THE AESTHETIC RECEPTION OF THE QURAN IN INSTAGRAM: Variations, Factors, and Religious Commodification - Purnama, Rizal Faturohman (ULUL ALBAB Jurnal Studi Islam, 2020)
This research discusses the aesthetic reception of the Quran in Instagram including various forms, appearance factors and commodification. This research is included in the qualitative study using Ahmad Rafiq’s reception theory. Using descriptive-analytical method, the study found variations of the Quran’s aesthetic reception in Instagram which are in the form of verse continuation and the Quran recitation. The background factors of the Quran’s aesthetic reception in Instagram include normative factors the Quran’s verses showing kindness to those who teach and practice it; historical factor i.e. the past reality related to the Quran’s aesthetic reception done by the Arab community; and social factors showing high passion of self-expression in preaching. Instagram as a social media has modified the Quran’s aesthetic reception with several available facilities and featuresthat enables its users to express themselves concerning the identity of religious piety and economic commodities through several contents related to the Quran.